External transcutaneous ultrasound technique in the equine cricoarytenoideus dorsalis muscle: Assessment of muscle size and echogenicity with resting endoscopy. (6th February 2020) - Satoh, Masato; Higuchi, Tohru; Inoue, Satoshi; Miyakoshi, Daisuke; Kajihara, Ayako; Gotoh, Tadahiro; Shimizu, Yasuhito
Abstract: Background: Recent studies have assessed the cricoarytenoideus dorsalis muscle (CAD) using transoesophageal ultrasonography in equine recurrent laryngeal neuropathy (RLN). We assessed the CAD using the external transcutaneous ultrasound technique, which may constitute an easier method in horses. Objectives: To evaluate ultrasonographic imaging of the left cricoarytenoideus dorsalis muscle (LCAD) and right cricoarytenoideus dorsalis muscle (RCAD) as a diagnostic tool for RLN using the transcutaneous ultrasound technique. Study design: Cross‐sectional study. Methods: The axial plane thickness, cross‐sectional area and echogenicity of the LCAD and RCAD were measured using transcutaneous ultrasonography in 164 horses. Assessments of LCAD were compared with those of RCAD. The LCAD:RCAD ratios in thickness and area were compared between control horses (resting grades 1 and 2) and horses with resting laryngeal grades 3 and 4 using the Havemeyer 4‐point grading system with subgrades. Results: The LCAD:RCAD ratios for thickness and area were 0.69 and 0.66 in horses with resting grades 3 and 4 respectively; LCAD was more hyperechogenic than RCAD in resting grades 3 and 4. LCAD:RCAD ratios for thickness and area in grades 3.II, 3.III and 4 were significantly lower than those in control horses. Thickness and area of the LCAD were negatively correlated with resting laryngeal grade Main limitations: Overground endoscopy was not performed in this study. There were some differences in methodology: measurement of the physical thickness of the LCAD and clipping of hair at the laryngeal region were only performed in horses that underwent laryngoplasty. Conclusions: Results of ultrasonographic assessments of the CAD using transcutaneous ultrasonography were similar to those obtained by transoesophageal ultrasonography. This technique enables a simple, noninvasive, direct and easy examination. Assessment of the CAD using transcutaneous ultrasonography may be a useful technique and a potential option for determining whether to perform nerve graft or laryngoplasty.